Tetrakis(3-cyanopyridine-κN (1))bis(thiocyanato-κN)cobalt(II) 1,4-dioxane disolvate - Diehr, Stephan (International Union of Crystallography, 2011)
In the crystal structure of the title compound, {[Co(NCS)(2)(C(6)H(4)N(2))(4)]·2C(4)H(8)O(2)}, the Co(II) cations are octahedrally coordinated by two terminal N-bonded thiocyanate anions and four N-bonded 3-cyanopyridine ligands. The asymmetric unit consists of one Co(II) cation, which is located on a special position with site symmetry 2/m, one thiocyanate anion and one dioxane molecule, located on a crystallographic mirror plane, as well as one 3-cyanopyridine ligand in a general position. The crystal structure consists of discrete complexes of [Co(NCS)(2)(3-cyanopyridine)(4)], as well as two non-coordinating 1,4-dioxane solvent molecules which are disordered due to symmetry.